2019
DOI: 10.1111/1462-2920.14489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sterol and fatty acid profiles of chytrids and their hosts reveals trophic upgrading of nutritionally inadequate phytoplankton by fungal parasites

Abstract: Summary Chytrids are ubiquitous fungal parasites in aquatic ecosystems, infecting representatives of all major phytoplankton groups. They repack carbon from inedible phytoplankton hosts into easily ingested chytrid propagules (zoospores), rendering this carbon accessible to zooplankton. Grazing on zoospores may circumvent bottlenecks in carbon transfer imposed by the dominance of inedible or poorly nutritious phytoplankton (mycoloop). We explored qualitative aspects of the mycoloop by analysing lipid profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 52 publications
1
57
0
Order By: Relevance
“…Eukaryotic fungi are potentially an important resource in aquatic ecosystems, especially in streams (Krauss et al, 2011). The same applies to chytrids, ubiquitous fungal parasites in aquatic ecosystems, providing a sterol source to their grazers even in absence of their phytoplankton hosts (Gerphagnon et al, 2019). Cyanobacteria as prokaryotes do not produce sterols at all (Volkman, 2003).…”
Section: Main Producersmentioning
confidence: 99%
“…Eukaryotic fungi are potentially an important resource in aquatic ecosystems, especially in streams (Krauss et al, 2011). The same applies to chytrids, ubiquitous fungal parasites in aquatic ecosystems, providing a sterol source to their grazers even in absence of their phytoplankton hosts (Gerphagnon et al, 2019). Cyanobacteria as prokaryotes do not produce sterols at all (Volkman, 2003).…”
Section: Main Producersmentioning
confidence: 99%
“…Arguably, rather than a consequence of low food quality per se (i.e. lack of sterols and long-chain poly-unsaturated fatty acids in cyanobacteria; Gerphagnon et al, 2018), our results could also be partially explained by the reported antifungal properties of M. aeruginosa (Sánchez et al, 2019). While the genus Planktothrix has not been tested for its antifungal properties against Daphnia parasites, it produces a wide array of bioactive secondary metabolites (Kurmayer, Deng, & Entfellner, 2016), that are likely to be involved in the defence against fungal chytrid parasites (Rohrlack, Christiansen, & Kurmayer, 2013;Sønstebø & Rohrlack, 2011).…”
Section: Parasite Fitnessmentioning
confidence: 99%
“…The role of essential lipids in determining the food quality of Planktothrix for zooplankton grazers has not been explored yet. However, sterol production by fungal parasites (chytrids) infecting Planktothrix filaments has been suggested to upgrade the poor food quality of Planktothrix for higher trophic levels (Gerphagnon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%